Relationship between Voriconazole Concentration and Invasive Aspergillosis Treatment Outcome: Efficacy and Safety - C, Puttilerpong; M, Tantasawat; Ayudhya, Panomvana Na; P, Chantarit (IIUM Medical Journal Malaysia, 2019)
Introduction: This study aimed to determine the association between the voriconazole (VRZ) concentration and clinical outcomes, including both the efficacy and safety in invasive aspergillosis (IA) treatment. Methods: The medical records of adult Thai patients with IA and treated with VRZ at the Ramathibodi Hospital, Thailand, between January 2013 and March 2016 were retrospectively reviewed, and their medical, social, demographic, laboratory data, VRZ dosage regimens and concentrations, and clinical outcome were recorded. The association between the VRZ concentration and clinical outcome was then determined. Results: A total of 81 patients were included in this study. Forty (49.4%) patients were male, with median age of 56.1 years. Sixty of them had hematologic malignancies. Forty-seven patients were diagnosed with probable IA. Median blood sampling time for VRZ level measurement was 11.5 h after the last dose administration on day 9. The median duration of treatment and outcome evaluation was 103 days and 73 days, respectively. Overall success and mortality rate were 76.5% and 14.8%, respectively. In the treatment success group, we found the success rate of around 90% with VRZ trough concentration (Ctr) of 3-4 mg/L. Eleven patients developed liver injuries (LI) and the rate of LI increased significantly with VRZ Ctr of more than 5 mg/L. Conclusion: We recommend VRZ trough concentration of 3-4 mg/L, as at this range the patients responded better to the treatment than at > 5.0 mg/L since it was associated with augmented hepatotoxicity.